2018
DOI: 10.1080/14786419.2018.1511555
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antifungal activity of essential oils from Senecio nutans, Senecio viridis, Tagetes terniflora and Aloysia gratissima against toxigenic Aspergillus and Fusarium species

Abstract: Essential oils from aerial parts of Senecio nutans, Senecio viridis, Tagetes terniflora and Aloysia gratissima were analysed by GC-MS and their antifungal activities were assayed on toxigenic Fusarium and Aspergillus species. Sabinene (27.6±0.1%), αphellandrene (15.7±0.3%), o-cymene (9.6±0.2%) and β-pinene (6.1±0.2%) in S. nutans, 9,10-dehydrofukinone (92.7±0.2%) in S. viridis, β-thujone (36.1±0.1%), αthujone (32.2±0.2%), 1,8-cineol (10.7±0.1%) and sabinene (6.2±0.2%) in A. gratissima, and cis-tagetone (33.6±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…This result was confirmed by the work of Abu-Darwish [ 43 ]. The richness in thujone of this oil could explain its effectiveness against dermatophytes, even though several works reported it was active on both bacteria and fungi [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result was confirmed by the work of Abu-Darwish [ 43 ]. The richness in thujone of this oil could explain its effectiveness against dermatophytes, even though several works reported it was active on both bacteria and fungi [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another hydrogen sesquiterpene, α-zingiberene, is also the main constituent of the S. selloi essential oil from Brazil [28]. Dehydrofukinone is by far the most important compound observed in the case of S. viridis from Argentina, since it constitutes more than 92% of the essential oil [29]. This comparison with other closely related species of Asteraceae suggests that the P. herzogii specimens that yielded this essential oil were phytochemically original, based on the high proportions of monoterpenic ethers.…”
Section: Resultsmentioning
confidence: 95%
“…Another hydrogen sesquiterpene, α-zingiberene, is also the main constituent of the S. selloi essential oil from Brazil [ 28 ]. Dehydrofukinone is by far the most important compound observed in the case of S. viridis from Argentina, since it constitutes more than 92% of the essential oil [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Galvez et al [ 20 ] reported that the essential oil from the aerial parts of A. gratissima shows moderate antifungal activity against toxigenic Fusarium (MIC = 0.6–1.2 mg/mL) and was mainly inactive against Aspergillus species.…”
Section: Resultsmentioning
confidence: 99%